Cerebral Aneurysms Treated with Flow-Diverting Stents: Computational Models with Intravascular Blood Flow Measurements - Levitt, M.R.; McGah, P.M.; Aliseda, A.; Mourad, P.D.; Nerva, J.D.; Vaidya, S.S.; Morton, R.P.; Ghodke, B.V.; Kim, L.J. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Computational fluid dynamics modeling is useful in the study of the hemodynamic environment of cerebral aneurysms, but patient-specific measurements of boundary conditions, such as blood flow velocity and pressure, have not been previously applied to the study of flow-diverting stents. We integrated patient-specific intravascular blood flow velocity and pressure measurements into computational models of aneurysms before and after treatment with flow-diverting stents to determine stent effects on aneurysm hemodynamics. MATERIALS AND METHODS: Blood flow velocity and pressure were measured in peri-aneurysmal locations by use of an intravascular dual-sensor pressure and Doppler velocity guidewire before and after flow-diverting stent treatment of 4 unruptured cerebral aneurysms. These measurements defined inflow and outflow boundary conditions for computational models. Intra-aneurysmal flow rates, wall shear stress, and wall shear stress gradient were calculated. RESULTS: Measurements of inflow velocity and outflow pressure were successful in all 4 patients. Computational models incorporating these measurements demonstrated significant reductions in intra-aneurysmal wall shear stress and wall shear stress gradient and a trend in reduced intra-aneurysmal blood flow. CONCLUSIONS: Integration of intravascular dual-sensor guidewire measurements of blood flow velocity and blood pressure provided patient-specific computational models of cerebral aneurysms. Aneurysm treatment with flow-diverting stents reduces blood flow and hemodynamic shear stress in the aneurysm dome. CFDcomputational fluid dynamicsWSSwall shear stressWSSGwall shear stress gradientTCDtranscranial Doppler ultrasonographypcMRAphase-contrast MRA